The structure and psychological meaning of a word. (Eurasian Journal of Philology Science and Education, 2015)
The meaning of a word is a complicated phenomenon. Along with the deep study of the semantic structure of words, their meaning in modern lingual system is also studied from the aspect ofverbal communication, which compiles psycholinguistic aspect. The study of the meanings from the psychological side includes their dynamic peculiarities and informative qualities of the word meaning. If we take into consideration the dependency of the functions of a word from the dynamic features, their situational, contextual and other factors the meaning of a word may be represented as the psychological phenomenon. This meaning of a word from the psychological aspect represents the unit of all the psychological actions, which are fixed in our memory by means of notions. But if on one hand from this point of view the meaning of a word is a complicated dynamic and changeable structure which is apt to the consistency, on the other hand from the linguistic point it is a steady, particular system which compiles only the part of this elaborate structure. The psychological structure of the meanings is closely related to the inner lexicon which is situated in the lingual consciousness and should be represented as the systematic organization of lexical meanings in the human memory. So, the humanity completely embraces 2 aspects of a word: the meaning(linguistic) and the sense(psychological).First of all, a person knows the permanent meaning of the words, and secondly a person is able to choose the sense of consumption and the system of mutual lexical connections in different situations.
Keywords: meaning; sense; psychological meaning; psycholinguistics; dynamic feature of the meaning; psychological structure of the meaning; verbal communication